Moderating Effect of Company Size on the Relationship between Tax Planning, Deferred Tax Expenses and Earnings Management - Saminem Saminem; Agustina Indriani; Reko Saprianto; Novi Dwi Haryati (Jurnal Akuntansi Indonesia, 2024)
ABSTRACTThis study aims to explore whether tax planning and deferredtax expenses influence earnings management, with companysize acting as a moderating variable. The research samplewas selected through purposive sampling, consisting of 16annual reports from food and beverage companies listed onthe Indonesia Stock Exchange (IDX) for the period 2018-2022.The analysis was conducted using regression and quantitativemethods. The results show that deferred tax expenses havea positive and significant effect on earnings management,whereas tax planning has a significant negative effect. Moreover,company size moderates the relationship between tax planningand earnings management. However, company size does notmoderate the relationship between deferred tax expenses andearnings management. Therefore, these findings contribute tothe literature by demonstrating that company size moderates theimpact of tax planning on earnings management in the food andbeverage industry and has important implications for investorsin the Indonesian market. Additionally, the study highlights thatlarger companies tend to develop better tax planning strategies,which in turn enhances transparency and accountability.